The kiasu culture and herd behaviour in Singapore - Choy, Ruth Hui Yi (2017)
The kiasu culture and its implications on Singapore have been topics of contention for many years. Social observers have noted that the kiasu culture has had a significant effect on herding behaviour among individuals in Singapore. In this paper, we develop a model under the framework suggested by Bikhchandani, Hirshleifer and Welsh (1991) to theoretically investigate this effect. Our findings suggest that all players who are risk-averse in their relative wealth exhibit an extremely strong tendency to follow the actions of players before them and attain the same relative wealth positions as before. Our research has potential extensions in the field of socio-economics, particularly in public policy development and decision-making within groups of individuals marked by similar competitive nature.